2012
DOI: 10.1002/cplu.201200206
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐Assisted In Situ Synthesis of Graphene/PEDOT Hybrid and Its Application in Supercapacitors

Abstract: A graphene/poly(3,4‐ethylenedioxythiophene) (G/PEDOT) hybrid was prepared by the in situ polymerization of 3,4‐ethylenedioxythiophene using the precursor of graphene, graphene oxide, as an oxidant under microwave heating. The G/PEDOT hybrid was characterized by ultraviolet–visible absorption spectroscopy, Fourier transform infrared spectroscopy, atomic force microscopy, X‐ray photoelectron spectroscopy, field‐emission scanning electron microscopy, energy‐dispersive X‐ray spectroscopy, and electrochemical imped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(33 citation statements)
references
References 53 publications
0
30
0
3
Order By: Relevance
“…The cycle stability test of PEDOT-SSC showed a capacitance retention of 86.2% after 20 000 cycles at 5 A/g. The above results are among the best performance parameters of PEDOT-based symmetric and asymmetric supercapacitors, as shown in Table 1 [35,37,39,4043]. According to the EIS analysis in Fig 5C, the small series resistance of PEDOT-SSC ( Re of 7.36 Ω and Rct of 0.88 Ω included) ensured fast charge transport between the electrode and electrolyte and may also have caused the well-defined cycling stability of the device.…”
Section: Resultsmentioning
confidence: 99%
“…The cycle stability test of PEDOT-SSC showed a capacitance retention of 86.2% after 20 000 cycles at 5 A/g. The above results are among the best performance parameters of PEDOT-based symmetric and asymmetric supercapacitors, as shown in Table 1 [35,37,39,4043]. According to the EIS analysis in Fig 5C, the small series resistance of PEDOT-SSC ( Re of 7.36 Ω and Rct of 0.88 Ω included) ensured fast charge transport between the electrode and electrolyte and may also have caused the well-defined cycling stability of the device.…”
Section: Resultsmentioning
confidence: 99%
“…그래핀 계열 물질과 PEDOT/PSS의 복합체에서 sulfur는 PEDOT/ PSS쪽에만 존재하므로 복합체 중의 sulfur 함량으로부터 복합체 중의 그래핀 함량을 측정하는 것이 일반적인 방법이다 [13,20,22]. PEDOT/ PSS에서의 sulfur 함량은 8.28%, 본 연구에서 합성한 GO-P의 경우에 는 4.78%로 나타났으며, 동일한 방법으로 계산한 GO-P 중의 GO 함 량은 42%로 나타났다.…”
Section: Go-p의 분석unclassified
“…이와 같은 특성 에 더해서 π전자가 풍부한 GO의 특성을 활용하여 π-π 상호작용에 의해서 다양한 고분자와의 복합화 [10,11]가 시도되었으며, 특히 전도 성 고분자인 polythiophene의 유도체와 π-π 상호작용으로 복합화한 GO가 광촉매로서 매우 유용한 것으로 나타났다 [12]. 동일한 상호작용 에 의해 최근 투명전극용으로 주목을 받고 있는 polythiophene 치환체 인 3,4-ethylene dioxythiophene (EDOT)과 GO의 복합화도 가능하며, 이와 같은 현상을 기초로 하여 microwave 하에서 GO에 의한 EDOT 의 중합 [13] 및 산화도가 높은 GO (highly oxidative GO)에 의해서 EDOT의 올리고머가 생성되는 현상 [14] 등도 보고되어있다. …”
unclassified
“…As another class of supercapacitors electrode material, graphene has attracted great interest due to its high theoretical surface area, good thermal and mechanical stability and high electrical conductivity [13]. Graphene/conductive polymer hybrids have attracted great deal of attention because they may possess novel combinations with superior electrochemical characteristics than either of the individual components [14][15][16][17]. Among them, it has been already confirmed that the hybrids consisted of polyaniline and graphene possess the superior electrochemical properties than either of the individual components, which are potential materials for the development of high-rate and stable supercapacitor electrodes [18,19].…”
Section: Introductionmentioning
confidence: 99%